Growth & Reproduction of Mustelus mustelus (Chondrichthyes: Triakidae) in the south Mediterranean (Libyan coast) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2019)
A total of 370 Mustelus mustelus have been collected monthly, directly from fishermen at the western coast of Libya (South Mediterranean) between November 2015 and December 2016. Each individual was measured, weighted, dissected to investigate the growth, age determination and spawning season. The largest fish was 168 cm, this size is considered the first record for M. Mustelus in the Mediterranean Sea, the weight was ranged from 365.5g to 20000g. the growth showed positive allometric growth (b = 3.2) gathered sex, also the von Bertalanffy growth model was described as K= 0.03, T0= -9.31 for M. mustelus and L∞ =194.9 cm. The age was ranged from one to 28 years and the majority age group is 4 years. The parturition occurring during the late April and May, after a gestation period of October and November in this area. This study highlights the biological aspects of M. Mustelus in the Libyan coasts in an attempt to fill the gap of knowledge on the Chondrichthyes species in the southeastern Mediterranean coast.
Keywords: Shark; growth; Mediterranean; fertility; Libya